To Compare the Efficacy and Safety Profile of Total thyroidectomy with Near Total Thyroidectomy for Benign Multinodular Goiter: A District Headquarter Hospital Experience - ARSHAD FARZOOQ, FAREEHA HUMAYOUN, MOHAMMAD NASIR, WASEEM MUHAMMAD, (Journal of Fatima Jinnah Medical University, 2018)
Background: The objective of this study is to compare Total Thyroidectomy with Near Total Thyroidectomy in terms of efficacy and safety. Total thyroidectomy is currently the preferred treatment for thyroid Cancer and benign multinodular goiter. However, many surgeons do not perform total thyroidectomy to treat benign thyroid diseases owing to the associated risk of postoperative hypoparathyroidism and recurrent laryngeal nerve damage. In our research we compared total thyroidectomies performed for benign thyroid diseases with near total thyroidectomy in order to assess whether the results support the hypothesis that total thyroidectomy is safe and can be considered as the optimal surgical approach for treating benign thyroid diseases. Materials and Methods: 250 patients with multinodular goiter were selected for the study from August 2008 to August 2013 at District Headquarter Hospital Kohat KPK, Pakistan. Patients were divided equally in two groups Group A and B (125 patients each). All patients were euthyroid. Group A patients underwent Near Total Thyroidectomy whereas Group B patients Total Thyroidectomy. Results were analyzed in terms of efficacy and in both group using SPSS program. Results: Group A (125 patients) underwent near total thyroidectomy and Group B(125 patients) underwent total thyroidectomy. In Group A patients undergoing Near Total Thyroidectomy, 18 patients (14%) with recurrence were found to have carcinoma on histopathological assessment of the removed gland and 10(8 %) patients had recurrence of goiter in follow up. Out of the total 28, 20 patients having recurrence were re-operated out of which 10 patients were reported to have carcinoma. Post operatively after first procedure 2 patients had recurrent Laryngeal nerve injury (1.6%) in near Total and 01 in Total Thyroidectomy Patients. Incidence of recurrent laryngeal nerve injury increased to 20% in second surgery in cases of patients undergoing Near total thyroidectomy as first procedure. 4 patients were offered Radioiodine ablation and the remaining 4 refused treatment amongst Carcinoma Thyroid patients. Recurrence in Total Thyroidectomy patients was 0% Conclusion: Total thyroidectomy is a safe alternative for patients with benign multinodular goiter due to low complication rate and also the procedure eliminates the need for reoperation for recurrent goiter and unexpected malignancy.